Pathogens associated with pleuritic pig lungs at an abattoir in Queensland Australia. Issue 5 (9th March 2021) - Turni, C; Meers, J; Parke, K; Singh, R; Yee, S; Templeton, J; Mone, NK; Blackall, PJ; Barnes, TS
Abstract : Objective: Pleurisy in pigs has economic impacts in the production stage and at slaughter. This study sought to establish if some micro‐organisms can be found in high numbers in lungs with pleurisy by assessing batches of pigs at an abattoir in Queensland Australia. Design: Samples of lung (including trachea/bronchus and lymph nodes) from a maximum of 5 pleurisy affected pigs were collected from 46 batches of pigs representing 46 Queensland farms. Procedure: Pleurisy‐affected lung areas were cultured by traditional bacteriological methods and bacteria quantified by plate scores. Additionally, tracheal or bronchial swabs and apical lobe fluid were tested for Mycoplasma hyopneumoniae DNA and the superior tracheobronchial lymph nodes were tested for porcine circovirus type 2 DNA by polymerase chain reaction (PCR). All apparently significant bacteria were identified via PCR or sequencing. Typing was undertaken on some of the bacterial isolates. Results: The most prevalent pathogens were M. hyopneumoniae, Streptococcus suis and Porcine Circovirus type 2, being found in 34, 38 and 31 batches, respectively. Other bacteria found were Actinobacillus species (29 batches), Pasteurella multocida (24 batches), Mycoplasma flocculare (9 batches), Actinobacillus pleuropneumoniae (7 batches), Mycoplasma hyorhinis (4 batches), Bisgaard Taxon 10 (1 batch), Glaesserella parasuis (1 batch), Streptococcus minor (1 batch) and Streptococcus porcinus (1 batch). Most batches had more than one bacterial species. Conclusion: The high percentage of batches infected with S. suis (83%), M. hyopneumoniae (74%) and PCV2 (70%) and clustering by a batch of these pathogens, as well as the presence of many secondary pathogens, suggests synergy between these organisms may have resulted in pleurisy.